Failure of Phenotypic Markers to Accurately Identify Black Bass Species and Associated Hybrids in the Mobile River Basin, Alabama. (17th September 2021) - Lewis, Matthew R.; Silliman, Katherine E.; Beck, Benjamin; Sammons, Steven M.; Peatman, Eric J.
Abstract: Hybridization among the black basses Micropterus spp. occurs due to weak postzygotic reproductive barriers and anthropogenic factors, such as habitat alteration. Introduction of previously allopatric species can also result in hybrid swarms and, in some cases, extirpation of native species. Introgressive hybridization is a major conservation concern for the more range‐restricted black basses, which underscores the need for accurate identification of hybrids that often have cryptic phenotypes. To that end, we collected 1, 723 fish from four river systems in the Mobile River basin, Alabama, to compare phenotypic identification in the field based on morphology with genotype determined from single‐nucleotide polymorphism analysis using diagnostic markers for black basses. Results indicated that phenotypic identification among these cryptic hybrids was only 11% accurate. Only 4% of the fish collected were identified as hybrids in the field, whereas genotype analysis classified 22% of the fish as hybrids. The majority of those misidentified in the field were hybrids between Alabama Bass M. henshalli and Redeye Bass M. coosae or between those species and another black bass species. Hybrid individuals composed 5–38% of the total number of fish collected from the four river systems, but 28–68% were misidentified in each river system. These results underscore the need for genetic tools to augment classic field surveys of the black basses, as cryptic hybridization may lead to errant management decisions based on inaccurate species distribution assessments.